The Influence of Medication Days’ Supply on Adherence and Cost of Hypertensive Patients at Primary Health Care Centre - Setiawan, Catur Dian; Wathaniah, Nurul; Rahmaniah, Atikah; Maharani, Primanda Ayu; Achmad, Gusti Noorrizka Veronika; Mufarrihah, Mufarrihah; Mahmudah, Azzahroh Sifaâ€™ Lailiyah (Indonesian Journal of Pharmacy, 2017)
Primary Health Care Centre is known have policy discrepancy with the supply of medicines. This can influence the adherence and costs incurred by patients. The study aimed to identify the influence for hypertensive patients at Primary Health Care Centre in Surabaya. This study was designed cross sectional and data collection was done by using ARMS questionnaires for the patient's adherence and interview for the cost. Cost was calculated based on the frequency of real visits and monthly patient expenditures. Direct medical cost, direct non medical cost, and indirect cost were included based on patients’ perspective. Direct observations were done to calculate the days of drug supplies. A total of 406 patients from 50 Health Care Centre were included in the study. Days of drug supplies ranged from 3 to 30 days; total ARMS scores ranged from 12 to 33; and the total cost obtained ranged from IDR 34,965 to IDR 239,528. The Spearman’s correlation test sought to obtain the significant influence of medication days’ supply on adherence with p value 0.0001 and r = -0.347. While medication days’ supply didn't show any significant influence on the cost. It will be significant if the patient met the visit schedule, that was p value 0.0001 and r = -0.247. It is recommended to prolong antihypertensive days’ supply in order to improve patients' adherence, as well as to reduce cost expensed by patients.